Measurement of particle production from the MICE Target - Soler, F.; Walaron, K.; Booth, C.; Carson, Michael; Hodgson, P.; Howlett, L.; Smith, P.; Adams, D.; Edgecock, R.; Murray, W.; Tilley, K.; Cobb, J.; et al. (2008)
This article describes the prototype target and the requirements for the target mechanism needed to provide a beam of muons to the Muon Ionization Cooling Experiment (MICE) from the ISIS accelerator at RAL. The mechanism has achieved the required 85g acceleration to be able to insert the target into the ISIS beam during the last 2 ms of the accelerating period. A prototype target test was used to integrate the target into ISIS and to measure the ISIS beam envelope, particle yields and beam loss, showing good agreement between data and simulations. © 2008 American Institute of Physics.